Envenomation by Bothrops snake in the City of Afuá, Ilha de Marajó, Pará State, Brazil - Silva, Elder Oliveira da (2019)
INTRODUCTION: Bothrops snakes are responsible for most of the envenomations in Pará State and Brazil, with acute inflammatory activity and coagulation changes as the main manifestations. OBJECTIVE: To report a severe case of envenomation by Bothrops snake occurred in the City of Afuá, Ilha de Marajó, Pará State, in 2015. CASE REPORT: Male of 15 years of age was bitten on the left leg while extracting palm heart from Euterpe oleracea (açaizeiro). The patient was admitted to the hospital 7 h after the snakebite referring to intense local pain, showing ascending edema to the thigh, ecchymosis, local bleeding, nausea, vomiting, epigastralgia, and altered urine color. RESULTS: Envenomation was classified as a serious accident and indicated 12 ampoules of antibotrope serum. Laboratory tests revealed leukocytosis, thrombocytopenia, coagulation disorders, and presence of red blood cells, proteins, leukocytes, and hemoglobin in the urine. At less than 48 h, the coagulation was normalized. In the evolution, bubbles and local necrosis appeared with the presence of purulent secretion. Metronidazole and chloramphenicol were used with good clinical response. The patient was discharged without severe sequelae after nine days. CONCLUSION: The description is intended to inform the scientific community and health professionals about the clinical manifestations and laboratory alterations caused by Bothrops envenomation, snakes found on Ilha de Marajó.